2018
DOI: 10.1039/c8ta03839b
|View full text |Cite
|
Sign up to set email alerts
|

Reversible facile Rb+and K+ions de/insertion in a KTiOPO4-type RbVPO4F cathode material

Abstract: In this paper, we report on a novel RbVPO4F fluoride phosphate, which adopts the KTiOPO4 (KTP) type structure and complements the AVPO4F (A = alkali metal) family of positive electrode (cathode) materials for metal-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…Generally, the PBE flavor of the exchange‐correlation potential overestimates experimental lattice constants of phosphates by 1–2 % . Considering a similar behavior of PBE for the LiNaCoPO 4 F phases, the cell parameters for Co 2+ in a high spin state indeed exceed the experimental values by 0–2 %, confirming that Co 2+ is in a high spin state, which was also previously validated by magnetic susceptibility measurements for 3D‐LiNaCoPO 4 F …”
Section: Resultssupporting
confidence: 77%
“…Generally, the PBE flavor of the exchange‐correlation potential overestimates experimental lattice constants of phosphates by 1–2 % . Considering a similar behavior of PBE for the LiNaCoPO 4 F phases, the cell parameters for Co 2+ in a high spin state indeed exceed the experimental values by 0–2 %, confirming that Co 2+ is in a high spin state, which was also previously validated by magnetic susceptibility measurements for 3D‐LiNaCoPO 4 F …”
Section: Resultssupporting
confidence: 77%
“…[16] Galvanostatic intermittent titration technique (GITT) analysis further confirms the fast K + diffusion within the KTP structure ( Figure S16). Electrochemical impedance spectroscopy (EIS) show that, upon activation, the charge transfer resistance (R ct )d ecreases from 4387 to 773 W after 100 cycles,w hich is substantially smaller than those of WS 2 ( % 1671 W), Dynamics simulations using bond balance energy landscape (BVEL) and climbing image nudged elastic band (CI-NEB) methods are conducted to unveil the origin of the fast K + -diffusion kinetics.A ss hown in Figures 4a-c and S17, the BVEL method reveals that K + ions preferentially migrate through aone-dimensional (1D) helical pathway along the baxis,similar to that of Rb + in RbVPO 4 F. [18] K + migration along the a-and c-axis are considered impassable due to extremely high energy barriers.W efurther calculate the energy barriers of the possible K + pathways via the CI-NEB method, the corresponding energy profiles are presented in Figures 4d-f. It is shown that the energy barriers along path 1, path 2, path 3 and path 4are 0.11, 0.15, 1.18 and 1.77 eV,respectively.These results again confirm the 1D helical K + -migration trajectory that is composed of path 1a nd path 2a nd possesses at otal energy barrier of as low as 0.15 eV (Figures 4d,S 17).…”
mentioning
confidence: 97%
“…In this work, we investigated and contrasted alkali ion (Li, Na, and K) intercalation properties in K x VPO 4 F ( x ∼ 0) by a combined experimental and computational study. Related work has been done by Fedotov et al and Nikitina et al Fedotov et al demonstrated that depotassiated K x VPO 4 F ( x ∼ 0.15) can intercalate Li ions reversibly, and found that Li ions occupy under‐coordinated sites, compared to K sites . Later, alkali ion diffusivity in K x VPO 4 F ( x ∼ 0.5) and Rb x VPO 4 F ( x ∼ 0.5) was investigated and compared by Nikitina et al and Fedotov et al, respectively .…”
mentioning
confidence: 96%
“…Related work has been done by Fedotov et al and Nikitina et al Fedotov et al demonstrated that depotassiated K x VPO 4 F ( x ∼ 0.15) can intercalate Li ions reversibly, and found that Li ions occupy under‐coordinated sites, compared to K sites . Later, alkali ion diffusivity in K x VPO 4 F ( x ∼ 0.5) and Rb x VPO 4 F ( x ∼ 0.5) was investigated and compared by Nikitina et al and Fedotov et al, respectively . These authors found that K migration along the c ‐axis has a low barrier (≈200 meV) and the Li ion diffusivity is lower than for Na and K ions in the K x VPO 4 F ( x ∼ 0.5) structure despite its smaller ionic size .…”
mentioning
confidence: 96%
See 1 more Smart Citation